2000
DOI: 10.1038/sj.mp.4000778
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in healthy humans is associated with orbital frontal chemistry

Abstract: The present study examines relationships between regional brain chemistry (as identified by localized in vivo three-dimensional single-voxel proton magnetic resonance spectroscopy (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 42 publications
(58 reference statements)
4
49
0
Order By: Relevance
“…Also in other disorders with dysbalanced impulsivity such as in borderline personality disorder, an increase in ACC glutamate levels has been described (Hoerst et al, 2010). In line with our results, glutamate concentrations in the frontal cortex of healthy subjects might depend on anxiety levels as revealed by a study of Grachev and Apkarian (2000). The authors showed that subjects with high levels of anxiety display an increased overall chemical activity in the frontal cortex by 430% compared with subjects with low levels of anxiety.…”
Section: Discussionsupporting
confidence: 79%
“…Also in other disorders with dysbalanced impulsivity such as in borderline personality disorder, an increase in ACC glutamate levels has been described (Hoerst et al, 2010). In line with our results, glutamate concentrations in the frontal cortex of healthy subjects might depend on anxiety levels as revealed by a study of Grachev and Apkarian (2000). The authors showed that subjects with high levels of anxiety display an increased overall chemical activity in the frontal cortex by 430% compared with subjects with low levels of anxiety.…”
Section: Discussionsupporting
confidence: 79%
“…Our correlational results at study endpoint add to an emerging literature relating NAA concentrations to anxiety variables, though the directionality and regional localization of the findings have been inconsistent across studies. In a non-clinical sample, NAA concentrations in the orbital frontal cortices were positively related to a composite measure of state and trait anxiety (55), while in social phobics, NAA/Cr in the ACC was found to be elevated and positively related to symptom severity (32). These divergent findings underscore the need for additional research, using consistent metabolite measures and ROIs, in discrete patient populations.…”
Section: Discussionmentioning
confidence: 73%
“…In our previous studies of different cognitive states (studies of anxiety, 36,37 pain, 38 anxiety and pain 39 ) using in vivo proton magnetic resonance spectroscopy ( 1 H-MRS), we demonstrated a sensitivity of the method for documentation of chemical-perceptual characteristics of the human personality, which can be captured by monitoring the regional changes of neuronal marker N-acetyl aspartate (NAA) in relation to specific cognitive measures. These studies already demonstrated that this approach could become a new method for tracking the long-term brain chemical characteristics of anxiety and pain, and, possibly some other cognitive states.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Thus, any changes in neuronal density/function and/or synaptic connections in the ACC of normal subjects might affect the SCW interference level (hypothesis to be tested). (2) NAA is a sensitive marker for several other cognitive states (depression (manuscript in preparation), anxiety and pain [36][37][38][39]. (3) This chemical is changed the most in neuropsychiatric disorders with abnormal interference (eg schizophrenia, 44,45 Alzheimer's disease, 46 bipolar disorder, 47 and anxiety disorders [48][49][50] ).…”
Section: Introductionmentioning
confidence: 99%